Pola Permintaan Komoditi Pertanian untuk Konsumsi di Provinsi Riau - Gevisioner; Febriamansyah, Rudi; Ifdal; Tarumun, Suardi (Badan Riset dan Inovasi Daerah (BRIDA) Provinsi Riau, 2015)
This study aims to analyze the pattern of food demand for consumption and calculate the population food demand in the Riau province until 2025. In the study we use descriptive and quantitative approach and Desirable Dietary Pattern (DDP) in analyzing the data and information.. Data used in this research was secondary data. The results of our analyses indicate that the quality of food comsumed by Riau residents do not meet the standard of PPH , because the food was still dominated by the food which come from grains, oils and fats and sugar group. Consequently, the needs variety of strategic food in Riau province were predicted to increase significantly in 2025 in line with the increase in the population number and in income. The demand for cassava and sweet potatoes would increase significantly compared to other food. While the demand for rice 1.63 percent annually. Total demand for rice would reach 787,140 ton, followed by vegetables at 510. 320 ton, 331.792 ton of fruits. To meet the food needs of Riau population there needs to increased in food production as well as farmers welfare, develop and revitalize the institution for food processing and marketing in rural areas and to improve the efficiency and effectiveness of food distribution. The knowledge of community about food and nutrition is also needed to increase. Food security planning with desirable dietary pattern (DDP) approach should be done consistently and correctly.